Implementation of Exclusive Breast Milk to Mothers With Small Nipples - Nora Rahmanindar; Seventina Nurul Hidayah; Evi Zulfiana (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
During breastfeeding, mothers gave a variety of excuses for not breastfeeding their infants, such as multiparous mothers who may be less aware of breastfeeding because they believe their milk supply is running low and mothers with small nipples who find it challenging to breastfeed due to nip damage caused by improper breastfeeding or care for the infant. breast. Both of these factors can make a mother anxious, which stops the oxytocin hormone from working, causing breast milk to be retained in the breast and the mother to switch to formula milk. In Kudaile Village, Tegal Regency, this study intends to examine the variables that affect women with cracked nipples applying exclusive breastfeeding. Finding factors that affect the adoption of exclusive breastfeeding is the specific goal of this study, which can help to increase. This study employs an observational design and a qualitative methodology. In-depth interview procedures were used to gather the data in accordance with the rules for interviewing and watching people. Field notes were made in addition to recording the interview outcomes. The researcher employed source triangulation, which involves gathering information from various sources (informant families) using the same.